I survived : the shark attacks of 1916 - Ball, Georgia; Tarshis, Lauren (I survived (Graphic novel series), 2020)
"Chet Roscow is finally feeling at home in his uncle's little New Jersey town. He has three new friends, and they love cooling off in the creek on hot summer days. But then comes shocking news: A massive shark has been attacking swimmers in the ocean along the Jersey Shore, not far from where Chet is staying. Fear is in the air. So when Chet spots a gray fin in the creek, he's sure it's his imagination running wild. It's impossible he's about to come face-to-face with a killer shark right?"--